Coolifting® CoolCell®, A New Group of Highly Effective Active Ingredients for the Reduction of Cellulite in Women - Hernán Pinto (Journal of Tissue Repair and Regeneration, 2018)
Cellulite is a very frequent clinical condition that, despite not being serious, constitutes one of the greatest aesthetic concerns of a large number of women. In recent years, some of the technologies that have allowed the development of devices and key tools in aesthetic medicine treatments have been consolidated. The aim of this article is to test the effectiveness of CoolCell®, a new treatment for cellulite that is administered with Coolifting® technology. We included 24 women who received 8 sessions of Coolifting® CoolCell®, one per week. Thermographic measurements were taken and satisfaction questionnaires were completed. Thermographic analysis showed a statistically significant color variation and self-assessment reports revealed that more around 75% of the subjects witnessed great or spectacular changes on their skin.
Keywords: cellulite